A Two‐Step Method Synthesis and Gas Sensing Properties of CoSnO3 Nanoparticles. Issue 25 (4th July 2019) - Li, Ting; Lin, Zhidong; Fu, Ping; Wang, Shenggao; Chen, Zhe; Zhang, Xiaowen; Liu, Liming
Abstract: A new type of multi‐metal oxide gas‐sensing material, CoSnO3 was synthesized by a simple hydrothermal method, in which CoSn(OH)6 was used as a precursor, and it was calcined into amorphous CoSnO3 . The CoSnO3 nanoparticles were characterized by means of XRD, FE‐SEM, TEM and N2 adsorption‐desorption analysis. The average size of the CoSnO3 nanoparticles was of 90 nm. The sensor based on the CoSnO3 nanoparticles showed good gas‐sensing performances to n‐butanol. The highest response was about 23 to 100 ppm n‐butanol at 200 °C. Moreover, CoSnO3 nanoparticles exhibits promising candidate material for fast, sensitive and selective detection of n‐butanol. Abstract : Mesporous CoSnO3 have been successfully prepared by a simple hydrothermal reaction. The mesporous CoSnO3 is composed of amorphous nanoparticles with grains size of 90 nm. The gas sensor based on the mesoporous CoSnO3 shows good response to alcohols gas, especially to n‐butanol. The sensitivity of the CoSnO3 sensor to 100 ppm n‐butanol is 22.3 at 200 °C. The sensor presents high gas‐sensing performances to n‐butanol including excellent selectivity, high sensitivity, low working temperature and good repeatability.